Cervical Spinal Fracture and Other Diagnoses Associated With Mortality in Hospitalized Ankylosing Spondylitis Patients. Issue 2 (February 2017) - Wysham, Katherine D.; Murray, Sara G.; Hills, Nancy; Yelin, Edward; Gensler, Lianne S.
Abstract : Objective: Little data exist regarding mortality in ankylosing spondylitis (AS). We assessed diagnoses associated with in‐hospital mortality in AS using a population‐based inpatient data set. Methods: Data were abstracted from the Healthcare Cost and Utilization Project Nationwide Inpatient Sample between 2007 and 2011. We identified AS admissions using International Classification of Diseases, Ninth Revision, Clinical Modification code 720.0. In‐hospital mortality was the primary outcome. Logistic regression was used to evaluate the association between top diagnoses and in‐hospital mortality. We performed a secondary analysis from the same years in all patients (with and without AS) with cervical spine (C‐spine) fracture to determine whether AS was an independent risk factor for mortality. Results: Between 2007 and 2011, we identified 12, 484 admissions and 267 deaths in AS patients. C‐spine fracture with spinal cord injury and sepsis had the highest odds of death, with odds ratios (ORs) of 13.43 (95% confidence interval [95% CI] 8.00–22.55, P  < 0.0001) and 7.63 (95% CI 5.62–10.36, P  < 0.0001), respectively. In the same time period, there were 53, 606 C‐spine fracture admissions, of which 408 were coded with AS. Among all C‐spine fracture hospitalizations, an AS diagnosis was associated with inpatient death (OR 1.61 [95% CI 1.16–2.22], P  = 0.004). Conclusion: In AS patients admitted to the hospital, C‐spine fracture is a leading cause of in‐hospital mortality. Other diagnoses associated with mortality include sepsis, pneumonia, cardiovascular disease, and comorbid illnesses. Among all hospitalizations with C‐spine fracture, AS was associated with increased odds of death. C‐spine fracture–associated mortality warrants further study to elucidate risk factors in order to prevent such devastating fractures in AS patients.